Freight transportation in logistics industry of Singapore- a feasibility study on autonomous trailers - Ngai, Chin Pang (2018)
Increase in world consumption has prompted increase in world trade and motivated more container ocean transport. This prompts more containers to pass through seaports to be transported to its final destination inland. Inland container haulage operations are required to complete the last mile delivery of containers from ports to warehouses. However, maintaining operations in status quo will result in shortage of trailer drivers in the future, given that older drivers are retiring and there is increasing difficulty to recruit younger locals into the logistics industry. Autonomous, otherwise known as driverless, trailers become an explored option to resolve this challenge. While Singapore government ministries and private companies have begun involvement in autonomous vehicles, autonomous trailers are still not tested in Singapore public roads yet, putting Singapore behind countries who have trialled them in public roads. Therefore, it is worthy to explore the possibility of implementing autonomous trailers in Singapore roads and to evaluate its feasibility. A feasibility study is conducted by combining anecdotal and mathematical analyses, such that it achieves a mix of qualitative and quantitative explanatory power. The anecdotal analysis is conducted via interviews with seven parties from various sectors with vested interest in autonomous trailers deployment, while mathematical analysis involved development of simplified mathematical model and applying them to two hypothetical scenarios on autonomous trailers’ deployment. The interviews revealed safety concerns of managing uncertainties with driver and pedestrians’ behaviour, high cost concerns, and ongoing process of developing comprehensive regulations for public operation as some main inhibitors to autonomous trucks’ implementation. The simplified mathematical model suggests higher feasibility if a dedicated lane for autonomous trailers is put in place. Although when evaluated collectively, it presents a feasibility score only slightly above the arbitrary passing mark for the potential in implementation, it is undeniable that government agencies are investing more resources in autonomous vehicles development. This provides the drive for more positive evaluation, as many concerns are expected to be addressed with advancements in autonomous trailers technology. However, insights from the feasibility study should also be revised in the future, as the change in conditions would have major impacts on the viewpoints held today.